Implementation of Character Education Value in the Short Film "Adipati Blek" - Maharani, Adinda (Jurnal Pendidikan Ilmu Sosial, 2022)
Character education is one of the basic elements that can shape an individual's personality. Today, the value of character education is considered to be fading, especially for teenagers who have dropped out of school. This causes them to be entangled in social deviations such as joining the motorcycle gang community to the punk community. The short film Adipati Blek is one of the methods implemented by researchers in providing character education for out-of-school teenagers. This study uses a qualitative approach, with the method of cultural analysis in the aspect of cognitive anthropology. The data collection technique used is a documentation literature study. The results showed that, with the Adipati Blek film, it could implement the values of character education such as hard work, positive thinking, and motivation to have self-confidence. Films can be a creative medium for out-of-school teenagers to explore what potential they have, so that they can achieve success according to what they can.